2006
DOI: 10.1152/ajpcell.00635.2005
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine's protection against cellular injury is dependent on heat shock factor-1

Abstract: Glutamine (GLN) has been shown to protect cells, tissues, and whole organisms from stress and injury. Enhanced expression of heat shock protein (HSP) has been hypothesized to be responsible for this protection. To date, there are no clear mechanistic data confirming this relationship. This study tested the hypothesis that GLN-mediated activation of the HSP pathway via heat shock factor-1 (HSF-1) is responsible for cellular protection. Wild-type HSF-1 (HSF-1(+/+)) and knockout (HSF-1(-/-)) mouse fibroblasts wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 34 publications
3
60
0
5
Order By: Relevance
“…It plays an important role as a carrier of nitrogen and carbon. Glutamine inhibits protein degradation and is an important precursor for glutathione synthesis (32)(33)(34). Due to the increased glutamine requirement in sepsis, the non-essential amino acid glutamine relatively becomes an essential amino acid.…”
Section: Discussionmentioning
confidence: 99%
“…It plays an important role as a carrier of nitrogen and carbon. Glutamine inhibits protein degradation and is an important precursor for glutathione synthesis (32)(33)(34). Due to the increased glutamine requirement in sepsis, the non-essential amino acid glutamine relatively becomes an essential amino acid.…”
Section: Discussionmentioning
confidence: 99%
“…21 Hamiel et al 22 found that Gln metabolism enhances HSP70 expression by increasing the hexosamine biosynthetic pathway activity, with the O-glycosylation, nuclear translocation, and transcriptional activation of Sp1 and heat shock factor-1 (HSF1) being responsible. Zachara et al 23 reported that stress (including thermal stress) applied to cells rapidly increases the O-glycosylation of intracellular proteins, which is associated with increased HSP70 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that Gln enhances the expression of Hsp (26)(27)(28)(29), which serves a key regulatory role in α-Syn degradation. Therefore, the regulation by Gln on Hsp70 expression in PC12 neuroblastoma cells was investigated.…”
Section: Gln Upregulates Hsp70 Expression In Pc12 Neuroblastoma Cellsmentioning
confidence: 99%